Clinical study to evaluate the masking of enamel white spots with ICON on the anterior permanent teeth and to evaluate the stability of the color improvement with a follow-up of 6 months (Journal of Hama University, 2022)
The aim of this study was to evaluate the cosmetic results of ICON® on permanent teeth according to the application protocol proposed by the manufacturer, and to determine which etching time is more effective for obtaining high cosmetic results.The sample included 40 teeth of anterior permanent teeth, for Patients have a white spots on their anterior permanent teeth, the sample was divided into two groups randomly: a group was eached by Hydrochloric acid (HCL 15%) once for two minutes, and a group was eached by Hydrochloric acid (HCL 15%) twice for two minutes, after that, ICON® was applied on the lesions, and after phase of treatment, follow-up periods (immediately after treatment –3 month - 6 months). To evaluate the color of the lesions, digital images were taken by professional camera (Canon 80D), with macro lens (Sigma 105mm), and then relying on the method of measuring digital image analysis techniques, and that is done by Photoshop program (Adobe Photoshop Version: 21.0.3 2020-California, U.S).The results showed the difference was insignificant between the 2 minutes and the 4 minutes etching groups, and the results were stable until the end of assessment periods.Conclusion: Conclude from this study that masking the white spot lesions with ICON® on buccal surfaces of the permanent front teeth has a good effect when applying etching material for a period of 2 or 4 minutes, the difference was insignificant between the two times. The ICON® infiltration results are considered constant for a period of six months